The first degree teaching teaching for students with visual disabilities: Systematizing scientific studies - Oliveira, Verônica Momberg Marques de; Lagoeiro, Aline de Cássia Damasceno (Revista Hipótese, 2022)
Intending to contribute to the teaching work of mathematical content, this research aimed to carry out a systematic review of research aimed at teaching first degree equations for visually impaired students, available in the CAPES Thesis and Dissertations Catalog. As the most specific search resulted in no research found, we then searched for “visual impairment mathematics”. The second search resulted in nine articles, of which six are analyzed in this research. Finally, we explain the results obtained, the scarcity of research, the importance of the teacher, the difficulties in the classroom and a proposal for future research.